WAYS TO USE DIGITAL TECHNOLOGIES IN MODERN EDUCATION AND INCREASE DIGITAL LITERACY - Zokirova Muxlisa Xusniddin qizi (Modern American Journals, 2025)
In this article, the measures for the approval of the "Digital Uzbekistan - 2030" strategy and its effective implementation, the use of digital technologies in various fields, the measures that can be applied and implemented in this system, the measures to increase the digital literacy of the population and the formation of the skills of using digital technologies in education, the development of the ability to use the Internet, and thus the improvement of the education system are covered based on analytical opinions.
Keywords: Digital technologies